Characterization of treatment failure in HIV positive patients in the Colombian Caribbean region (Colombia Medica, 2014)
Objectives: Treatment failure in patients receiving antiretroviral therapy against human immunodeficiency virus (HIV) is always a concern. The major aim of the present work was to examine the correlates associated with treatment failure in patients living in the Colombian Caribbean city of Barranquilla, an aspect that was poorly studied in this region. Methods: Treatment failure was evaluated in a cross-sectional study from virological, immunological and clinical standpoints. Results: It was established that 29.5% of patients under highly active antiretroviral therapy (HAART) could be considered in treatment failure. Among those, virological failure was most frequent (20.9%), followed by immunological- (14.0%) and clinical failure (4.7%). In patients showing lack of adherence to the treatment, the likelihood of suffering from treatment- and virogical-failure were respectively increased by 6.67-fold and 12.19-fold, compared with patients showing good adherence. Although there was no statistically significant association, treatment failure tended to be more frequent in young adults and in patients with low income or low level of education. When antiretroviral therapies (ART) regimens were compared, there was no apparent difference in treatment failure between regimens based on non-nucleoside reverse transcriptase inhibitors and those based on protease inhibitors.  This is very important in the context of recent ART strategies, such as early-initiated ART, aimed at achieving long-term infection control. Conclusions: The current study confirms the importance of treatment adherence to avoid treatment failure and further highlights the importance of educating HIV-infected patients in all parts of the world, especially those individuals with a lower socio-economic status.